immuneACCESS
DOI: 10.21417/pl2018ji
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Exposure in the Elderly Does Not Reduce CD8 T Cell Repertoire Diversity

Abstract: With age, the immune system becomes less effective, causing increased susceptibility to infection. Chronic CMV infection further impairs immune function and is associated with increased mortality in the elderly. CMV exposure elicits massive CD8 + T cell clonal expansions and diminishes the cytotoxic T cell response to subsequent infections, leading to the hypothesis that to maintain homeostasis, T cell clones are expelled from the repertoire, reducing T cell repertoire diversity and diminishing the ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…At the other end of the age spectrum, when CMV is contracted in the elderly, a time where T cell numbers are mostly governed by slow, homeostatic expansion, memory inflation may become the primary mechanism that maintains and expands the CMV-specific T cell population. Moreover, our observation of increased TCR-β chain oligoclonality and diversity over time is in line with a report suggesting that while CMV may distort the repertoire in the elderly, the repertoire broadens to allow effective immune responses to some extent ( 55 , 56 ). However, whether the repertoire distortions reported in the present study and in previous reports would reflect the composition of the CMV-specific repertoire in lymphoid tissue remains unclear.…”
Section: Discussionsupporting
confidence: 92%
“…At the other end of the age spectrum, when CMV is contracted in the elderly, a time where T cell numbers are mostly governed by slow, homeostatic expansion, memory inflation may become the primary mechanism that maintains and expands the CMV-specific T cell population. Moreover, our observation of increased TCR-β chain oligoclonality and diversity over time is in line with a report suggesting that while CMV may distort the repertoire in the elderly, the repertoire broadens to allow effective immune responses to some extent ( 55 , 56 ). However, whether the repertoire distortions reported in the present study and in previous reports would reflect the composition of the CMV-specific repertoire in lymphoid tissue remains unclear.…”
Section: Discussionsupporting
confidence: 92%
“…These cross-sectional studies also demonstrated that many of these T cells remained polyfunctional despite having a highly differentiated phenotype [39, 44, 46, 5054]. In addition it has been shown that the total CD8 + T cell pool (based on absolute numbers) expands to accommodate these CMV-specific expansions [52, 55]. Other studies have demonstrated a decline in the absolute numbers of naïve T cells in older age irrespective of CMV sero-status [23, 56].…”
Section: Does Memory Inflation Of Cmv-specific T Cell Responses Occurmentioning
confidence: 99%
“…An important open question is how exposures to many antigens over a human lifetime collectively shape our T cell repertoire (Farber et al, 2014;Davis and Brodin, 2018). High-throughput repertoire sequencing enables direct surveys of the diversity and clonal composition of T cells from human blood or tissue samples and thus promises to provide quantitative answers to this question (Robins et al, 2009;Thomas et al, 2014;Britanova et al, 2016;Emerson et al, 2017;Oakes et al, 2017;Thome et al, 2016;Robins et al, 2010;Qi et al, 2014;Lindau et al, 2019;Joshi et al, 2019). However, while the TCR locus provides a natural barcode for clonal lineages due to its large diversity, this same diversity also makes inferring past clonal dynamics a challenging inverse problem, in particular given practical limitations on sequencing depth and temporal resolution in longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%